STUDENT'S PERCEPTION ON USING GOOGLE CLASSROOM IN DISTANCE LEARNING - Rahmiati; Saiful; Sujariati (FKIP Unismuh Makassar, 2022)
This research focused on the students perception on using Google Classroom in distance learning. This research used a mixed methods. The subject of this research was the 30 students taken from class XI MIA 4 (Natural Science). The data of the students perception on using Google Classroom in distance learning were obtained from the result of the questionnaire and interview. The result of this research indicated a positive response from the students. The findings showed that of the 20 items on the questionnaire, strongly agree and agree have the highest percentage of positive statements. Strongly agree had a percentage of 3,3-30% and agree had a percentage of 3,3-60%. Meanwhile, interview results show that using Google Classroom makes it easier for students in the distance learning process, and the challenges faced by students were not understanding the material and network connections.